2007
DOI: 10.1111/j.1570-7458.2007.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid‐based colour polyphenism in a moth species: search for fitness correlates

Abstract: Carotenoid‐based integumental coloration is often associated with individual performance in various animals. This is because the limited amount of the pigment has to be allocated to different vital functions. However, most of the evidence for the carotenoid‐based trade‐off comes from vertebrate studies, and it is unclear if this principle can be applied to insects. This possibility was investigated in Orgyia antiqua L. (Lepidoptera: Lymantriidae). The larvae of this species are polyphenic in their coloration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 57 publications
(61 reference statements)
2
33
0
2
Order By: Relevance
“…Pigments such as carotenoids act to add coloration to the insect integument (Sandre et al 2007), and a general association between dark integument and a reduced likelihood of mortality from parasitoids has been observed in a natural assemblage of tree-feeding caterpillars (Barbosa and Caldas 2007). In addition, Ojala et al (2005) found that arctiid larvae consuming plant diets with high carotenoid concentrations had increased melanization responses.…”
Section: Discussionmentioning
confidence: 97%
“…Pigments such as carotenoids act to add coloration to the insect integument (Sandre et al 2007), and a general association between dark integument and a reduced likelihood of mortality from parasitoids has been observed in a natural assemblage of tree-feeding caterpillars (Barbosa and Caldas 2007). In addition, Ojala et al (2005) found that arctiid larvae consuming plant diets with high carotenoid concentrations had increased melanization responses.…”
Section: Discussionmentioning
confidence: 97%
“…However, we were unable to demonstrate an effect of host plant on larval colour pattern (Sandre et al, 2007), nor was the colour pattern dependent on rearing temperature (Sandre et al, in press). Notably, however, the frequency of colour morphs was found to differ between larval instars: most typically (but not invariably) a larva is pied in its 4th instar, bright in the 5th, and dull in the 6th instar (Sandre et al, 2007) with the larvae switching from one morph to another in connection to moulting. From the data analysed at the level of particular instars, it remained unclear if such a pattern is primarily attributable to larval instar, body size, or sex.…”
Section: Study Speciesmentioning
confidence: 97%
“…In holometabolous insects at least, it is common that younger, smaller-bodied developmental stages are cryptic, and the aposematic species acquire their typical warning colouration in their later larval instars, or in the adult stage (Bernays & Montllor, 1989;Ulmer et al, 2003;Sandre et al, 2007). However, following the rationale of the trade-off hypothesis, one should expect also an ontogenetic change in the opposite direction, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations